2008
DOI: 10.1007/s12630-008-9023-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane on carrageenan- and fentanyl-induced pain hypersensitivity in Sprague-Dawley rats

Abstract: Purpose Opioids are widely used for anesthesia but paradoxically induce postoperative pain hypersensitivity via N-methyl-D-aspartate (NMDA) receptor modulation. Sevoflurane effects on opioid-induced hyperalgesia have not been yet evaluated in vivo. Nevertheless, some experimental in vitro studies reported anti-NMDA receptor properties for sevoflurane. The aim of this study was to evaluate sevoflurane effects on fentanyl-induced hyperalgesia in opioid-naive rats and in rats with inflammatory pain. Methods Sevof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…26,27 Although sevoflurane prevents sensitization by inhibiting the N-methyl-d-aspartate receptor, this effect cannot sufficiently prevent chronic pain. 28 Anesthetics did not show significant effects on the severity of chronic pain. We are unsure of the interpretation of this finding.…”
Section: Discussionmentioning
confidence: 89%
“…26,27 Although sevoflurane prevents sensitization by inhibiting the N-methyl-d-aspartate receptor, this effect cannot sufficiently prevent chronic pain. 28 Anesthetics did not show significant effects on the severity of chronic pain. We are unsure of the interpretation of this finding.…”
Section: Discussionmentioning
confidence: 89%
“…However, propofol has been shown to be able to prevent remifentanil-induced hyperalgesia in volunteers 65 and patients after surgery, 18 whereas sevoflurane has only weak anti-hyperalgesic effects in fentanyl-induced hyperalgesia in rat. 66 In conclusion, the prevention by propofol of the development of remifentanilinduced hyperalgesia and related consequences in patients after surgery deserve further clinical evaluation.…”
Section: The Prevention Of Remifentanil-induced Hyperalgesia In Surgimentioning
confidence: 97%
“…However, Solt et al (2006) documented that sevoflurane has only a minimal inhibitory effect on NMDA receptors, which are considered to be involved in the development of opioid-related hypersensitivity (Tompkins and Campbell, 2011). Relatively low sevoflurane concentrations (1.0%) reverse OIH, but there was the lack of effect of sevoflurane concentrations of 1.0 and 1.5% to oppose hyperalgesia following high-dose opioids (Solt et al, 2006; Richebe et al, 2009). Shin et al (2010) also suggested that remifentanil-induced hyperalgesia was not apparent during propofol anesthesia compared with the effect produced during sevoflurane anesthesia even though dosage of remifentanil was increased from 1.0 to 4.0 ng/ml.…”
Section: Factors That Lead To Discrepancies Regarding Aot and Oihmentioning
confidence: 99%